Discrepancy between Self-Reported and Actual Phonics Content Knowledge of Government Primary School Teachers in Pakistan - Malik, Sadia; Asif, Saiqa Imtiaz; Saleem, Nasir (Journal of Communication and Cultural Trends, 2023)
The discrepancy between teachers’ self-reported and actual knowledge can be lethal for any pedagogic process. In that case, they cannot achieve the learning objectives by transferring the required knowledge and skills among the learners. This research intends to explore the gap between phonics-related self-reported and actual knowledge of Pakistani government primary school teachers to see how far they are competent in phonics knowledge. This investigation further elucidates the quality of pre-and in-service teacher preparation programs in equipping the primary grade instructors with the required skill. For this purpose, 230 government primary school teachers were asked to report their phonics knowledge through a Likert scale questionnaire. In addition, a section of 10 MCQs was added to assess their actual knowledge of which different aspects of phonics, i.e., the definition of phonics, number of sounds in the English language, identifying consonant and vowel digraphs, short and long vowel sounds, number of sounds and syllable in a word and consonant blend. The findings realised the severe discrepancy between the self-reported and actual knowledge as only 28.3 % of teachers could score average or above-average marks, though the majority overrated their competence. Comparatively older, less qualified, and less professionally trained teachers with non-M.A. English qualifications were more prone to the tendency of overvaluing their knowledge. This situation implies that specific phonics content-based training is not provided to the teachers during pre-and in-service teacher preparation programs. However, the phonology of English is taught to them to some extent; teacher knowledge is not assessed at any stage. These findings propose content-based teacher training, teacher knowledge assessment, and the incorporation of technology to facilitate teachers.